Biomass aerogel reinforced asphalt material and preparation method thereof

By mixing biomass aerogel with asphalt, a biomass aerogel-enhanced asphalt material is formed, which solves the problem of asphalt materials prone to cracking in high-altitude areas, significantly improves thermal insulation performance and crack resistance, extends the service life of the road and improves driving safety.

CN119592089AInactive Publication Date: 2025-03-11HARBIN MADIER CULTURAL TOURISM INVESTMENT GROUP CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411817446.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing asphalt materials are prone to cracking in high-altitude areas, resulting in road safety hazards, and their thermal insulation performance is not sufficient to cope with temperature changes.

Method used

By mixing the biomass aerogel with asphalt, a biomass aerogel-enhanced asphalt material is formed, and the porous structure of the aerogel is used to improve the thermal insulation properties and crack resistance of the asphalt material.

Benefits of technology

It significantly improves the thermal insulation performance of asphalt materials, slows down the fluctuations in road surface temperature, reduces the possibility of road surface cracking, extends the service life of the road, and improves driving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592089A_ABST
    Figure CN119592089A_ABST
Patent Text Reader

Abstract

The invention relates to the field of road construction materials, and particularly provides a biomass aerogel reinforced asphalt material and a preparation method thereof. The material is a mixture of asphalt and biomass aerogel, the biomass aerogel accounts for 1-15 wt% in the mixture, and the size of the biomass aerogel is 100-700 [mu] m. The method comprises the following steps: S1, treating ramie to obtain oxidized cellulose; s2, preparing biomass aerogel by using the oxidized cellulose through a sol-gel method and an ice template method; s3, mixing the biomass aerogel with asphalt to obtain a mixture. The aerogel is introduced, so that the heat insulation performance of the asphalt material is improved; therefore, when the surface temperature is low in an alpine region, heat is not easy to conduct from top to bottom, the temperature rise amount of the roadbed on the lower side is small, the roadbed is not easy to soften, and therefore the road is prevented from being broken; the crack resistance is obviously improved. The material prepared through the method is good in heat insulation performance and suitable for alpine regions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of road construction materials, and in particular, to a biomass aerogel-enhanced asphalt material and a preparation method thereof. Background Art

[0002] Generally, roads include roadbed, road subbase, road base, and surface layer. The roadbed is the lowest structure of the road, which is in direct contact with the natural soil and is the basis for providing stable support. The road subbase and road base are usually made of crushed stone and gravel, which need to have high strength and durability. The upper layer or the entire surface layer is asphalt, which is in direct contact with the vehicle tires, providing a flat, anti-skid, and wear-resistant surface, improving driving comfort and safety, and preventing moisture penetration to protect the underlying structure.

[0003] In high-altitude cold regions, the surface temperature of the road is low, and the heat accumulates in the lower layer of the road. That is, the heat from the road surface will be conducted downward, causing the road surface base to warm up and soften. At the same time, under the action of gravity, the shear stress perpendicular to the road surface applied by vehicles on the asphalt road surface increases, making the road surface very easy to crack. In addition, the heat generated by the increase in temperature or the friction of the road surface during vehicle driving will cause the melted ice and snow to penetrate the asphalt surface and erode the matrix, thereby aggravating the cracking of the road surface and posing a hidden danger to driving safety. Therefore, the existing asphalt materials are not suitable for high-altitude cold regions, and the asphalt materials need to be modified. Summary of the invention

[0004] The purpose of the present invention is to provide a biomass aerogel-enhanced asphalt material and a preparation method thereof in view of the deficiencies in the above-mentioned prior art, so as to solve the problem that the asphalt material in the prior art is not suitable for high-altitude cold areas and the asphalt material needs to be modified.

[0005] Temperature changes and vehicle travel are not controllable. To solve the problem of easy road cracking, we should start with asphalt materials. The reason for the cracking is that as the temperature decreases, the heat will be transferred downward, causing the base to soften, making it easy to crack under the shear force applied by the vehicle. If the thermal insulation performance of the asphalt material is improved, the heat will not be easily transferred downward, and the road surface will not be easy to crack. Therefore, the key to solving the problem is to improve the thermal insulation performance of the asphalt material.

[0006] As a lightweight, porous material, aerogel has excellent thermal insulation properties and resistance to temperature changes. This application uses aerogel to improve the thermal insulation properties of asphalt materials and slow down the temperature fluctuations of the road surface, thereby reducing the possibility of road cracking, in order to solve the problem of asphalt road cracking in high-cold areas. In addition, the porous structure of aerogel can also absorb and store a large amount of water, reducing the erosion of ice and snow meltwater on the road surface, further extending the service life of the road surface. Provide new ideas and solutions to solve problems such as cracking of asphalt pavements in high-cold areas. Make important contributions to increasing the service life of roads, reducing maintenance costs and improving driving safety.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows: The present application provides a biomass aerogel-enhanced asphalt material, which is a mixture of asphalt and biomass aerogel, wherein the biomass aerogel accounts for 1 wt%-15wt% of the mixture, and the size of the biomass aerogel is 100-700μm.

[0008] Furthermore, the biomass aerogel accounts for 5wt% of the mixture, and the size of the biomass aerogel is 500μm.

[0009] The present application also proposes a method for preparing a biomass aerogel-enhanced asphalt material, the method comprising the following steps: S1, treating ramie to obtain oxidized cellulose; S2, preparation of biomass aerogels using oxidized cellulose via sol-gel and ice-template methods; S3, mixing the biomass aerogel with asphalt to obtain a mixture.

[0010] Furthermore, step S1 includes the following steps: S11, washing, drying, shearing, and then delignifying the ramie; S12, soaking the ramie obtained in step S11 in the first mixed liquid, then adding the second mixed liquid to the first mixed liquid, and storing them in a sealed state at room temperature; S13, after being fully stirred in an oil bath, washing with deionized water to obtain oxidized cellulose.

[0011] Furthermore, the delignification treatment includes: placing the cut ramie in a mixture of sodium chlorite solution and acetic acid buffer; stirring for 12 hours in an oil bath at 80 °C; and then washing with deionized water and drying.

[0012] Furthermore, the first mixed solution is a sodium phosphate solution in which TEMPO and sodium chlorite are dissolved; and the second mixed solution is a mixed solution of sodium hypochlorite and sodium phosphate.

[0013] Furthermore, step S2 includes the following steps: S21, dissolving oxidized cellulose in the third mixed solution, stirring thoroughly, and refrigerating to obtain a cellulose sol; S22, MBA and cellulose sol are uniformly mixed, poured into the first mold, debubbled, and aged to obtain a hydrogel; S23, soaking the hydrogel in deionized water for multiple times until the pH of the solution is neutral, then transferring it to a second mold, performing directional freezing, and finally drying it to obtain a biomass aerogel.

[0014] Furthermore, the third mixed solution is a mixed solution of NaOH, urea and water, and the third mixed solution needs to be pre-frozen at -18°C for 12 hours.

[0015] Furthermore, step S3 includes the following steps: S31, heating a mixture of asphalt and petroleum ether to soften it, then adding ferric citrate, and then adding the crushed biomass aerogel, and mixing them thoroughly; S32, aged at 40-80 °C for 1-7 h, and then heated at 80 °C for 1 h to obtain a biomass aerogel-reinforced asphalt material.

[0016] Furthermore, the mass ratio of asphalt to petroleum ether is 1:0.5, and the mass fraction of the biomass aerogel added in step S31 is 5 wt%.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The introduction of aerogel improves the thermal insulation performance of asphalt materials; thus, in high-cold areas, when the surface temperature is low, heat is not easy to conduct from top to bottom, the temperature rise of the roadbed on the lower side is small, and it is not easy to soften, thus avoiding road rupture. Aerogel is a porous material with a large number of micron- and nano-scale pores inside. The porous structure of aerogel will scatter the flow of gas molecules and the transfer of heat, weaken the thermal conduction effect of solids, reduce the conduction of heat, and block the heat during the transfer process, thereby reducing the overall thermal conductivity. The internal voids of aerogel are filled with air, and the thermal conductivity of air itself is very low, which further reduces the conduction of heat, reduces the thermal conductivity of asphalt, and improves the thermal insulation performance. In addition, the porous structure of aerogel can also absorb and store a large amount of water, reduce the erosion of ice and snow melt water on the road surface, and significantly improve the durability of the road surface, especially for crack resistance and water damage resistance when used in cold areas. The materials prepared by the materials and methods of this application are suitable for high-cold areas. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1The SEM characterization results (magnified 1000 times) of the crushed aerogel during the preparation method of the biomass aerogel-enhanced asphalt material provided by the present invention; Figure 2 The SEM characterization results (magnified 5000 times) of the crushed aerogel during the preparation process of the biomass aerogel-enhanced asphalt material provided by the present invention; Figure 3 The thermal conductivity results of modified asphalt and ordinary asphalt for this application are compared; Figure 4 The dynamic modulus results of modified asphalt and ordinary asphalt for this application are compared; Figure 5 The phase angle results of modified asphalt and ordinary asphalt for this application are compared; Figure 6 The fatigue life results of modified asphalt and ordinary asphalt are compared for this application. DETAILED DESCRIPTION

[0019] In order to make the implementation process of the present invention clearer, it will be described in detail below with reference to the accompanying drawings.

[0020] The present invention provides a biomass aerogel-enhanced asphalt material, which is a mixture of asphalt and biomass aerogel, wherein the biomass aerogel accounts for 1 wt%-15wt% of the mixture, and the size of the biomass aerogel is 100-700μm. Aerogel has a rich macroporous structure, the pores are filled with air, and the thermal conductivity is low, so it has good thermal insulation performance. However, the mechanical strength of aerogel is low, and excessive addition will reduce the mechanical strength of asphalt. The amount of aerogel added is between 1 wt%-15wt%, which can greatly improve the thermal insulation capacity while maintaining the mechanical strength of asphalt. Preferably, the biomass aerogel accounts for 5wt% of the mixture, and the size of the biomass aerogel is 500μm. If the doping ratio is too small, it cannot play a good thermal insulation role, and if the doping ratio is too large, the mechanical strength of asphalt will be reduced. If the size of the aerogel is too large, it will also affect the mechanical strength of the mixed asphalt, but if the size is too small, the aerogel pores will be blocked by asphalt and lose thermal insulation performance. The asphalt can be any one of AC25, AC20, AC16, SBS16, or a mixture of several. Biomass raw materials are biological raw materials rich in cellulose, which can be ramie, corn stalks, sugarcane bagasse, banana tree cores, palm leaves, etc.

[0021] The present application also proposes a method for preparing a biomass aerogel-enhanced asphalt material, the method comprising the following steps: S1, treating ramie to obtain oxidized cellulose. Specifically, step S1 comprises the following steps: S11, wash, dry, and shear the ramie, and then perform delignification treatment. More specifically, wash the ramie with water to wash off the mud, dust, etc. on its surface. The cleaned ramie is placed in an electric hot air drying oven at 60 ° C for 24 hours to remove surface moisture; then cut the dried ramie into a length of 3 to 5 cm to facilitate soaking treatment. If it is too long, it is not easy to put it into a beaker, conical flask, or other container. Perform delignification treatment: put the sheared ramie into a mixed solution of sodium chlorite solution and acetic acid buffer; the concentration of the sodium chlorite solution is 1 wt%, and the pH of the acetic acid buffer is 4.6. In this embodiment, 100 mL of sodium chlorite solution and acetic acid buffer are taken respectively, and the ratio of ramie to the mixed solution is 100 mL: 1 g, and the mass of ramie added is 2 g; at this concentration and pH, the ramie fiber can be protected from being destroyed, which is conducive to forming a porous structure. The ratio of ramie to solution affects the fiber quality, and excessive ramie will cause insufficient treatment. Then, stirring in an 80 °C oil bath for 12 h can ensure the smooth completion of delignification without causing fiber breakage due to excessive temperature; delignification treatment can reduce the content of lignin, which will remain in the pores of the aerogel, resulting in a decrease in porosity and further reducing its thermal insulation performance. After delignification, the residual reagents were thoroughly washed off with deionized water, and then dried in an electric heated blast drying oven at 60 °C.

[0022] S12, the ramie obtained in step S11 is soaked in the first mixed solution, and then the second mixed solution is added to the first mixed solution, and the mixture is sealed and stored at room temperature for 12 hours. The first mixed solution is a sodium phosphate solution in which TEMPO (tetramethylpiperidinyl oxide) and sodium chlorite are dissolved, wherein the mass of TEMPO is 0.032g, the mass of sodium chlorite is 2.26g, the concentration of the sodium phosphate solvent is 0.1 mol / L, the volume is 200mL, and the pH value is 6.8; in the oxidation process of cellulose, TEMPO can selectively oxidize the C6 primary alcohol group of cellulose to a carboxyl group to generate oxidized cellulose nanofibers. The second mixed solution is a mixed solution of sodium hypochlorite and sodium phosphate, wherein the concentration of the sodium hypochlorite / sodium phosphate mixed solution is 0.1 mol / L, the volume is 20mL, and the pH value is 6.8. The solute and the solvent can be increased or decreased by the same multiple.

[0023] S13, after being fully stirred in an oil bath, washing with deionized water to obtain oxidized cellulose. Specifically, stirring in an oil bath at 60 °C for 48 h to soften the cellulose; finally, washing with deionized water to pH = 7, thereby obtaining TEMPO oxidized cellulose.

[0024] S2, using oxidized cellulose, preparing biomass aerogel by sol-gel and ice template method, specifically, step S2 comprises the following steps: S21, dissolving oxidized cellulose in the third mixed solution, stirring thoroughly, and refrigerating to obtain a cellulose sol. The third mixed solution is a mixed alkali solution, specifically a mixed solution of NaOH, urea, and water, with a corresponding ratio of 7:12:81. The third mixed solution needs to be frozen at -18 °C for 12 hours in advance to prepare for freeze drying. When oxidized cellulose is dissolved in the third mixed solution, the proportion of oxidized cellulose is 3 wt%. In this embodiment, 0.52 g of oxidized cellulose is added, stirred for two hours after addition, and then the stirred sample is placed in a refrigerator at 0~4 °C for 12 hours to prepare a cellulose sol.

[0025] S22, MBA (N,N'-methylenebisacrylamide) and cellulose sol were mixed evenly, poured into the first mold, debubbled, and aged to obtain a hydrogel. Specifically, 0.156 g of MBA was added to the cellulose sol, stirred for 1 h to fully mix it, and then poured into the first mold, which was a cylindrical mold; then, the cylindrical mold was placed in a vacuum drying oven and vacuumed for 15 minutes to remove bubbles, and the sample after debubbling was aged at room temperature for 24 h to achieve the purpose of cross-linking and prepare a hydrogel.

[0026] S23, soak the hydrogel in deionized water for many times until the pH of the solution is neutral, then transfer it to the second mold for directional freezing, and finally dry it to obtain biomass aerogel. Specifically, soak the hydrogel in deionized water for 24 hours, change the water 4 to 7 times in the middle until the pH is neutral, and then transfer the hydrogel to the second mold. The second mold is a hollow mold with a copper plate at the bottom and polystyrene foam (EPS) around. The bottom copper plate is in contact with liquid nitrogen, and the hydrogel will be directional frozen from the bottom to the top. The freezing temperature is -17 ° C; then, the frozen hydrogel is placed in a freeze dryer for freeze drying for 72 hours. After ice sublimation, a cellulose aerogel with vertically uniform distribution of pores is obtained. Specifically, during the directional freezing process, as the bottom gradually cools, water molecules begin to form a crystal structure at the freezing interface and grow upward. This freezing process from the bottom to the top will lead to the formation of vertically oriented microporous channels, which helps to enhance the mechanical properties and thermal insulation effect of the hydrogel. The microporous channels are connected in the vertical direction, but are discontinuous in the horizontal direction, which limits the conduction of heat in the horizontal direction; in the vertical direction, the air in the directional channels has a lower thermal conductivity, which further reduces the overall thermal conductivity. In addition, the vertically oriented channel structure can disperse the external stress and form a better support force in the horizontal direction, avoiding the collapse or deformation of the material, and improving the material's compressive resistance and stability.

[0027] Aerogels with vertically oriented microporous channels obtained by directional freezing are more compatible with asphalt. On the one hand, after freeze-drying and other treatments, the internal pores of the oriented microporous aerogel are highly directional, which reduces the tendency of aerogel particles to agglomerate during the mixing process. In non-oriented microporous or non-porous aerogels, it is easier to form agglomerates and the asphalt is unevenly dispersed. On the other hand, the pore structure in the oriented microporous aerogel greatly increases the specific surface area of ​​the material, increases the contact area between the aerogel and the asphalt, and is conducive to interfacial bonding; the fine structure in the pore can "accommodate" some asphalt molecules, embedding them into the micropores of the aerogel, thereby enhancing dispersibility and compatibility. On the other hand, the oriented microporous channels of the aerogel form a "guiding channel" in the asphalt, reducing the overall viscosity of the material during the mixing process, facilitating stirring and uniform dispersion; compared with dense non-porous aerogels, aerogels with microporous structures can make it easier for asphalt to penetrate and disperse in the structure, improving the uniformity of mixing.

[0028] S3, mixing the biomass aerogel with asphalt to obtain a mixture. Specifically, step S3 includes the following steps: S31, heat the mixture of asphalt and petroleum ether to soften it, then add ferric citrate, and then add the crushed biomass aerogel and mix them thoroughly. Biomass aerogel particles with a particle size of 500 µm are easier to disperse in asphalt, and the irregular particle shape also helps to "embed" into the asphalt matrix, forming a certain mechanical interlocking effect. The average particle size of the crushed biomass aerogel is 500 μm. The SEM characterization results are shown in Figure 1 and Figure 2 As shown in the figure, the aerogel is in irregular granular shape. Further magnification reveals that it has abundant pores inside. These pores can greatly reduce the thermal conductivity of the aerogel and improve the thermal insulation performance. The gas molecules will be reflected multiple times between the pore walls, producing a "bending effect", which in turn extends the movement path of the gas molecules, making heat transfer more difficult, increasing the thermal resistance of the aerogel, and playing an important role in improving the thermal insulation performance. A mixture of asphalt (BS16 is used in this example) and petroleum ether is heated at 50 oC for 1 h to soften it. The mass ratio of asphalt to petroleum ether is 1:0.5. Softened asphalt is easier to mix with aerogel. Petroleum ether also reduces the viscosity of asphalt, making it more fluid. The added aerogel is easier to be evenly distributed in the asphalt matrix, improving the compatibility of the two. Then add 0.1wt%-wt 1% stabilizer, which can be 0.2 wt% ferric citrate as a stabilizer. Too small a stabilizer ratio will cause the asphalt to solidify quickly, and too much stabilizer ratio will cause the asphalt to become brittle. The stabilizer can also be one of ferric nitrate, ferric chloride, and ferric acetylacetonate. The stabilizer plays a role in inhibiting the rapid solidification of asphalt, keeping the state of asphalt soft and fluid during the mixing process, so that the aerogel is fully dispersed in the asphalt. The stabilizer also enhances the combination between asphalt and aerogel particles through weak adsorption at the interface between asphalt and aerogel, thereby improving the compatibility of the system. Then add the crushed biomass aerogel and continue stirring for 2 hours to fully mix, reduce the aggregation of aerogel particles, and help the stabilizer to distribute on the interface between aerogel and asphalt, thereby improving compatibility; stirring also ensures that the pores of the aerogel are partially infiltrated, improving the structural stability of the overall composite material. The mass fraction of the added biomass aerogel is 5 wt%; when the mass fraction of the aerogel is too high, the particles may pile up on each other, resulting in uneven distribution, reducing the thermal insulation performance, and increasing the brittleness of the composite material, thereby reducing the overall mechanical strength; when it is too low, the thermal insulation performance is not significantly improved.

[0029] S32, aging at 40-80°C for 1-7h, and then heating at 80°C for 1h to obtain a biomass aerogel-enhanced asphalt material. o After aging at 80 °C for 4 h, o C, and heated for 1 h to remove the petroleum ether to obtain the biomass aerogel-enhanced asphalt material of the present application.

[0030] Figure 3 The thermal conductivity results of the modified asphalt (lower side, square pattern, black curve) and the ordinary asphalt (upper side, circular pattern, red curve) for this application are compared, showing the change of thermal conductivity with temperature. The black curve is below the red curve, at -20-40 o In the range of C, the thermal conductivity of the modified asphalt decreases and the thermal insulation performance improves. The asphalt material of the present application can play a good thermal insulation role, making it difficult for heat to be transmitted downward to the roadbed, and the roadbed is not easy to soften, so it will not break and form cracks. This is because the aerogel particles distributed in the asphalt have a low thermal conductivity, which hinders the rapid transfer of heat inside the asphalt.

[0031] Figure 4The dynamic modulus results of the modified asphalt (upper side, square pattern, black curve) and the ordinary asphalt (lower side, circular pattern, red curve) are compared; the black curve is above the red curve, and the dynamic modulus of the modified asphalt material increases. This shows that the mechanical strength of the modified asphalt is better maintained during the process of increasing the external temperature, which is due to the improvement of thermal insulation brought by the aerogel doping.

[0032] Figure 5 The phase angle results of the modified asphalt (lower side, square pattern, black curve) and the ordinary asphalt (upper side, circular pattern, red curve) are compared; the black curve is below the red curve, and the phase angle of the modified asphalt material decreases. This shows that the anti-cutting ability of the modified asphalt is also improved during the process of increasing the external temperature.

[0033] Figure 6 This is a comparison of the fatigue life results of the modified asphalt (upper side, square pattern, black curve) and the ordinary asphalt (lower side, circular pattern, red curve). The black curve is above the red curve, and the fatigue life of the modified asphalt material is significantly improved (GB / T 36143-2018). This shows that the modified asphalt has a longer service life and reduces maintenance costs.

[0034] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A biomass aerogel-enhanced asphalt material, characterized in that: The material is a mixture of asphalt and biomass aerogel, wherein the biomass aerogel accounts for 1 wt%-15wt% of the mixture, and the size of the biomass aerogel is 100-700 μm.

2. The biomass aerogel-enhanced asphalt material according to claim 1, characterized in that: The biomass aerogel accounts for 5wt% of the mixture, and the size of the biomass aerogel is 500μm.

3. A method for preparing a biomass aerogel-enhanced asphalt material, characterized in that: The method comprises the following steps: S1, treating ramie to obtain oxidized cellulose; S2, using the oxidized cellulose to prepare biomass aerogel by sol-gel and ice template methods; S3, mixing the biomass aerogel with asphalt to obtain a mixture.

4. The method for preparing the biomass aerogel-enhanced asphalt material according to claim 3, characterized in that: The step S1 comprises the following steps: S11, washing, drying, shearing, and then delignifying the ramie; S12, soaking the ramie obtained in step S11 in the first mixed liquid, then adding the second mixed liquid to the first mixed liquid, and storing them in a sealed state at room temperature; S13, after being fully stirred in an oil bath, washing with deionized water to obtain oxidized cellulose.

5. The method for preparing the biomass aerogel-enhanced asphalt material according to claim 4, characterized in that: The delignification treatment comprises: placing the cut ramie into a mixture of sodium chlorite solution and acetic acid buffer; stirring for 12 h in an oil bath at 80 °C; then, washing with deionized water and drying.

6. The method for preparing the biomass aerogel-enhanced asphalt material according to claim 5, characterized in that: The first mixed solution is a sodium phosphate solution in which TEMPO and sodium chlorite are dissolved; and the second mixed solution is a mixed solution of sodium hypochlorite and sodium phosphate.

7. The method for preparing the biomass aerogel-enhanced asphalt material according to claim 6, characterized in that: The step S2 comprises the following steps: S21, dissolving the oxidized cellulose in the third mixed solution, stirring sufficiently, and refrigerating to obtain a cellulose sol; S22, MBA and cellulose sol are uniformly mixed, poured into the first mold, debubbled, and aged to obtain a hydrogel; S23, soaking the hydrogel in deionized water for multiple times until the pH of the solution is neutral, then transferring the hydrogel to a second mold, performing directional freezing, and finally drying the mold to obtain the biomass aerogel.

8. The method for preparing the biomass aerogel-enhanced asphalt material according to claim 7, characterized in that: The third mixed solution is a mixed solution of NaOH, urea and water, and the third mixed solution needs to be pre-frozen at -18 °C for 12 hours.

9. The method for preparing the biomass aerogel-enhanced asphalt material according to claim 8, characterized in that: The step S3 comprises the following steps: S31, heating a mixture of asphalt and petroleum ether to soften it, then adding ferric citrate, and then adding the crushed biomass aerogel, and mixing them thoroughly; S32, aging at 40-80°C for 1-7h, and then heating at 80°C for 1h to obtain the biomass aerogel-reinforced asphalt material.

10. The method for preparing the biomass aerogel-enhanced asphalt material according to claim 9, characterized in that: The mass ratio of the asphalt to petroleum ether is 1:0.5, and the mass fraction of the biomass aerogel added in step S31 is 5 wt%.

Citation Information

Patent Citations

  • Preparation method of plant cellulose aerogel with bionic structure, high pressure resistance and high heat insulation performance

    CN115403823A

  • Preparation method of waste-paper-based cellulose aerogel and modified asphalt of waste-paper-based cellulose aerogel

    CN118930951A

  • Aerogel modified bituminous binders and mixtures

    US20240270969A1